Common variation in NCAN, a risk factor for bipolar disorder and schizophrenia, influences local cortical folding in schizophrenia. Issue 4 (March 2014) - Schultz, C. C.; Mühleisen, T. W.; Nenadic, I.; Koch, K.; Wagner, G.; Schachtzabel, C.; Siedek, F.; Nöthen, M. M.; Rietschel, M.; Deufel, T.; Kiehntopf, M.; Cichon, S.; et al.
<x content-type="archive" xml:space="preserve">Abstract</x> Background Recent studies have provided strong evidence that variation in the gene neurocan (NCAN, rs1064395) is a common risk factor for bipolar disorder (BD) and schizophrenia. However, the possible relevance of NCAN variation to disease mechanisms in the human brain has not yet been explored. Thus, to identify a putative pathomechanism, we tested whether the risk allele has an influence on cortical thickness and folding in a well-characterized sample of patients with schizophrenia and healthy controls. Method Sixty-three patients and 65 controls underwent T1-weighted magnetic resonance imaging (MRI) and were genotyped for the single nucleotide polymorphism (SNP) rs1064395. Folding and thickness were analysed on a node-by-node basis using a surface-based approach (FreeSurfer). Results In patients, NCAN risk status (defined by AA and AG carriers) was found to be associated with higher folding in the right lateral occipital region and at a trend level for the left dorsolateral prefrontal cortex. Controls did not show any association (p > 0.05). For cortical thickness, there was no significant effect in either patients or controls. Conclusions This study is the first to describe an effect of the NCAN risk variant on brain structure. Our data show that the NCAN risk allele influences cortical folding in the occipital and prefrontal cortex, which may establish disease susceptibility during neurodevelopment. The findings suggest that NCAN is involved in visual processing and top-down cognitive functioning. Both major cognitive processes are known to be disturbed in schizophrenia. Moreover, our study reveals new evidence for a specific genetic influence on local cortical folding in schizophrenia.